PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR - Roby Binur; Bambang Sahono (UNIB Press, 2023)
The purpose of this study is to, 1) increase student cooperation in the Science Lesson Content through the application of the Group Investigation Learning Model, 2) To improve student achievement in the Science Lesson Content through the implementation of the Group Investigation Learning Model, 3) To describe the effectiveness of the Group Investigation learning model implementation in improve student learning achievement in science lesson content in class V SD Negeri Gugus 1 Selagan Raya Mukomuko. In this study, the Class Action Research (CAR) method was used and continued with experimental research. The subjects of this study were grade 5 students of SD Negeri Gugus 1 Selagan Raya. Data collection techniques used in the study were observation sheets and student test methods. Analysis of the data used values ​​are 1) Analysis of teacher assessment instruments, 2) Analysis of student cooperation instruments, 3) Analysis of pre-test and post-test scores, 3) T-test analysis of student achievement. The instrument of cooperation and student achievement in the research used was the GI type of cooperative learning model. The conclusions of this study are: 1). The application of the GI type cooperative learning model can increase student cooperation in science subjects, 2). The application of the GI type cooperative learning model can improve student achievement in science subjects at SD Negeri Gugus 1 Selagan Raya in the first semester of the 2022/2023 academic year, and 3). The application of the GI type cooperative model is effective in increasing student collaboration and achievement compared to conventional learning models